Torula yeast (Candida utilis) on distiller?s vinasse in growing pig diets - Mora, Luis Marino; Lezcano, Pedro; Hidalgo, Katia; Rodr?guez, B?rbara (Cuban Journal of Agricultural Science, 2012)
Twenty-four Yorkshire-Landrace x Yorkshire growing pigs, of 98 d of age and 25.5 kg of liveweight were used to evaluate the substitution of imported soybean meal by torula yeast (Candida utilis), produced at national scale on distiller?s vinasse. The animals were allocated individually, according to completely randomized design. They were distributed into three treatments (0, 34 %, and 66 % of protein substitution), with eight repetitions each. There was not significant effect of the yeast level on the daily weight gain, the final liveweight and the feed conversion. The results suggested that up to 66 % of the protein from soybean can be substituted in this swine category. Studies are recommended to permit higher level of inclusion, as well as economic and environmental evaluations. Key words: yeasts, pigs, vinasse.